Biodistribution of samarium-153-EDTMP in rats treated with docetaxel - Villarim Neto,Arthur (2009)
PURPOSE: Many patients with metastatic bone disease have to use radiopharmaceuticals associated with chemotherapy to relieve bone pain. The aim of this study was to assess the influence of docetaxel on the biodistribution of samarium-153-EDTMP in bones and other organs of rats. METHODS: Wistar male rats were randomly allocated into 2 groups of 6 rats each. The DS (docetaxel/samarium) group received docetaxel (15 mg/kg) intraperitoneally in two cycles 11 days apart. The S (samarium/control) group rats were not treated with docetaxel. Nine days after chemotherapy, all the rats were injected with 0.1ml of samarium-153-EDTMP via orbital plexus (25µCi). After 2 hours, the animals were killed and samples of the brain, thyroid, lung, heart, stomach, colon, liver, kidney and both femurs were removed. The percentage radioactivity of each sample (% ATI/g) was determined in an automatic gamma-counter (Wizard-1470, Perkin-Elmer, Finland). RESULTS: On the 9th day after the administration of the 2nd chemotherapy cycle, the rats had a significant weight loss (314.50±22.09g) compared (p<0.5) to pre-treatment weight (353.66± 22.8). The % ATI/g in the samples of rats treated with samarium-153-EDTMP had a significant reduction in the right femur, left femur, kidney, liver and lungs of animals treated with docetaxel, compared to the control rats. CONCLUSION: The combination of docetaxel and samarium-153-EDTMP was associated with a lower response rate in the biodistribution of the radiopharmaceutical to targeted tissues. Further investigation into the impact of docetaxel on biodistribution of samarium-153-EDTMP would complement the findings of this study.